DAMPAK TRADISI METUAKAN SEBAGAI SARANA INTEGRASI SOSIAL PERILAKU MASYARAKAT - Komang Elit Arya Cahyaning; Komang Febrinayanti Dantes; I Wayan Empu Guana Pura (Universitas Pendidikan Ganesha, 2026)
The metuakan tradition is part of the local cultural heritage of the Balinese people that continues to exist today, particularly in the Karangasem region and several other villages. This tradition is closely associated with social gatherings where people enjoy traditional alcoholic beverages such as tuak or arak in an atmosphere of togetherness and camaraderie. This study aims to examine the influence of the metuakan tradition as a means of social integration within community behavior. The research employs a qualitative approach using a literature review method, involving the analysis of various journals, research articles, and other relevant academic sources. The findings indicate that the metuakan tradition has positive impacts on strengthening social relationships, enhancing solidarity, improving interpersonal communication, and serving as a medium for preserving local culture. However, the tradition may also have negative implications when practiced excessively, including health risks and social conflicts associated with uncontrolled alcohol consumption. Therefore, social supervision and public awareness are essential to ensure that the metuakan tradition continues to be practiced as a cultural heritage that emphasizes togetherness and social integration.